1983
DOI: 10.1016/s0022-5347(17)51706-1
|View full text |Cite
|
Sign up to set email alerts
|

Peyronie’s Disease and Erectile Failure

Abstract: A total of 20 patients with Peyronie's disease, including 15 with erectile failure and 5 with normal potency, underwent evaluation with dynamic xenon washout and infusion cavernosography. Abnormal drainage from the cavernous body was found in 13 of the 15 patients with erectile failure and in none of the 5 potent patients (p less than 0.01), indicating that this condition seems to be the underlying pathological mechanism leading to erectile impotence in patients with Peyronie's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 7 publications
2
21
0
2
Order By: Relevance
“…23 Metz et al showed abnormal venous drainage in 69% of Peyronie's patients with ED using dynamic Xenon washout and stated that VOD was primarily responsible for ED. 24 Gasior et al reported their results of DICC in Peyronie's patients with ED and found that 86% had evidence of VOD. 25 However, Lopez and Jarow were the ®rst to show that the high prevalence of VOD was unique to Peyronie's disease.…”
Section: Discussionmentioning
confidence: 99%
“…23 Metz et al showed abnormal venous drainage in 69% of Peyronie's patients with ED using dynamic Xenon washout and stated that VOD was primarily responsible for ED. 24 Gasior et al reported their results of DICC in Peyronie's patients with ED and found that 86% had evidence of VOD. 25 However, Lopez and Jarow were the ®rst to show that the high prevalence of VOD was unique to Peyronie's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative and qualitative alterations in the collagen post-fixed in 2% osmium tetroxide, dehydrated in graded ethanol and propylene oxide, and embedded in Epon and elastic fibres may render the tunica unable to compress the subtunical and emissary veins adequately, 812. Randomized tissue blocks from patients with and without Peyronie's disease were thick-sectioned (1 mm) resulting in veno-occlusive dysfunction [16][17][18].…”
mentioning
confidence: 99%
“…During detumescence, blood¯ow was initially elevated (20±75 mla100 gamin), and subsequently decreased to the¯accid levels 2.5±4 min after termination of the visual stimulation. In 1983, this group published results of intracavernosal injection of xenon in patients with Peyronie's disease, 31 a disorder which is frequently accompanied by erectile dysfunction. In ®ve patients with normal erectile function, normal venous closure was noted after onset of erection, similar to the ®nding previously noted in controls.…”
Section: Historical Development and Resultsmentioning
confidence: 99%